Changes in serum albumin and liver enzymes following three different types of bariatric surgery: six-month follow-up. A retrospective cohort study - Zadeh, Mohadeseh Hassan; Zamaninour, Negar; Ansar, Hastimansooreh; Kabir, Ali; Pazouki, Abdolreza; Farsani, Gholamreza Mohammadi (São Paulo Medical Journal, 2021)
BACKGROUND: Few reports have examined the effects of Roux-en-Y gastric bypass (RYGB), one-anastomosis gastric bypass (OAGB) and sleeve gastrectomy (SG) on changes to serum albumin (Alb) and liver enzyme levels. OBJECTIVE: To compare short-term post-surgery changes in serum Alb, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALKP) levels. Body composition changes were also measured and compared among three groups. DESIGN AND SETTING: Retrospective cohort study conducted in Tehran, Iran. METHODS: 151 OAGB, RYGB and SG patients referred to the obesity clinic of Hazrat-e Rasool General Hospital, Tehran, Iran, were evaluated. Physical characteristics and biochemical parameters were measured pre-surgery and then after three and six months. RESULTS: Through repeated measurements to determine intragroup changes, significant changes in serum AST (P = 0.003) and ALT (P < 0.001) were observed in follow-ups. However, Alb levels did not change (P = 0.413). Body fat, fat-free mass and muscle mass decreased significantly in each group (P < 0.05). In a univariate general linear model for determining intergroup changes, SG showed greater decreases in ALT and AST at three and six months (P < 0.05) and in ALKP at six months (P = 0.037), compared with OAGB. There were no significant differences in Alb levels. Also, RYGB had a greater effect on reducing fat percentage (three months, P = 0.011; six months, P = 0.059) and fat mass (three months, P = 0.042) than OAGB. CONCLUSION: SG and RYGB may be superior to OAGB in reducing liver enzymes and body fat, respectively. However, Alb levels showed no significant differences.